Proceedings of SPE Annual Technical Conference and Exhibition 2007
DOI: 10.2523/109915-ms
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Transport and Sorption Behavior in Confined Coal Cores for Enhanced Coalbed Methane and CO2 Sequestration.

Abstract: Measurements of sorption isotherms and transport properties of CO 2 in coal cores are important for designing enhanced coalbed methane/CO 2 sequestration field projects. Sorption isotherms measured in the lab can provide the upper limit on the amount of CO 2 that might be sorbed in these projects.Because sequestration sites will most likely be in unmineable coals, many of the coals will be deep and under considerable lithostatic and hydrostatic pressures. These lithostatic pressures may significantly reduce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…Therefore, coal core can not relax into its original status even the pressure load is removed at the final stage. Similar observation was noticed by Jikich et al (16) . They used x-ray CT to study the CO 2 adsorption in coal core.…”
Section: Density Logsupporting
confidence: 81%
See 1 more Smart Citation
“…Therefore, coal core can not relax into its original status even the pressure load is removed at the final stage. Similar observation was noticed by Jikich et al (16) . They used x-ray CT to study the CO 2 adsorption in coal core.…”
Section: Density Logsupporting
confidence: 81%
“…In literature there are limited studies related to the flow, storage mechanisms, and structure and property variation of coal. Several authors have demonstrated that x-ray CT can be a useful tool in studying the distributions of coal density (10) , minerals and cleat/fracture distribution (11,12,13) , and coal adsorption and swelling by CO 2 (2,14,15,16) . With the help of other image tools, x-ray CT can be used to investigate the gas storage and transport properties of coal (17,18,19) .…”
Section: Introductionmentioning
confidence: 99%
“…This would then impart enhanced molecular sieving in this region. To compare the loading level of CO 2 and CH 4 within the molecular representation, the same number of molecules (25) was added to the structure to visualize where in the structure the molecules would reside (Figures 5 and 7). Again, the methane molecules were false-colored yellow to aid in visualization.…”
Section: Resultsmentioning
confidence: 99%
“…In the last few years, disposal of carbon dioxide (CO 2 ) in permeable, porous subsurface rock formations (often known as geological sequestration) has been identified as a viable option for reducing greenhouse gas emissions into the atmosphere. Potential subsurface systems considered for geological sequestration include depleted oil and gas reservoirs, 1,2 coalbed methane and shale gas reservoirs, 3,4 and deep aquifers. 5,6 Though each of these disposal systems has its advantages, deep aquifers (mostly filled with nonpotable or brackish waters) have the greatest potential for large CO 2 sequestration programs, primarily because of their relative abundance in most sedimentary basins and their large effective capacities.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, disposal of carbon dioxide (CO 2 ) in permeable, porous subsurface rock formations (often known as geological sequestration) has been identified as a viable option for reducing greenhouse gas emissions into the atmosphere. Potential subsurface systems considered for geological sequestration include depleted oil and gas reservoirs, , coalbed methane and shale gas reservoirs, , and deep aquifers. , Though each of these disposal systems has its advantages, deep aquifers (mostly filled with nonpotable or brackish waters) have the greatest potential for large CO 2 sequestration programs, primarily because of their relative abundance in most sedimentary basins and their large effective capacities. , Successful selection of the potential of CO 2 deep aquifer sequestration sites, however, requires an understanding of all the physical and chemical trapping mechanisms by which CO 2 may be retained, where the stratigraphic/structural and residual fluid mechanisms have the largest and most immediate impact on trapping or retaining CO 2 in aquifers . A common attribute between the stratigraphic/structural and residual fluid mechanisms is the dependence on capillary pressure characteristics of the aquifer seal and formation, in which the capillary pressure characteristics are the strong functions of both the interfacial tension (IFT) properties of the water plus carbon dioxide (H 2 O + CO 2 ) system and the behavior of CO 2 -rich phase density.…”
Section: Introductionmentioning
confidence: 99%